Perioperative fluid therapy in adults and children: a narrative review - Lorente, Juan Victor; Hervías Sanz, Mónica; Ripollés-Melchor, Javier; Hahn, Robert G. (Frontiers in Medicine, 2025)
Intravenous fluid administration is an important part of the management of the surgical patient. Fluid can be used to compensate for the normal turnover of fluid and electrolytes (maintenance), to replace losses, to expand the extracellular fluid space to maintain adequate circulation (resuscitation), and to provide nutrition. Too little fluid and too much fluid both increase the number of postoperative complications. Balanced crystalloid solutions, such as buffered Ringer’s, Plasma-Lyte®, and Sterofundin®, are the most widely used fluids. Isotonic (0.9%) sodium chloride should be reserved for alkalotic and/or hyponatremic patients. Small amounts of these fluids (<500 mL) only expand the plasma volume, while larger volumes distribute to one or two interstitial fluid spaces as well. Filling of the second interstitial space (“third space”) greatly prolongs the half-life of the fluid The indications for colloid fluids are limited but include volume support in major hemorrhage when balanced crystalloids volume become large enough to cause adverse effects (>3 L). Maintenance fluids contain glucose and are indicated during the postoperative period before oral hydration is possible. Glucose might also be provided when awaiting surgery. The choice of replacement fluid is governed by the type of losses that have occurred. The goal of infusion fluids during hemorrhage or serious disease changes over time and might be described in the four phases resuscitation, optimization, stabilization, and de-resuscitation. Nutrition fluids are indicated after 1 week without adequate oral nutrition. Fluid therapy during surgery is performed according to the fluid balance approach (minor surgery), the outcome-oriented approach (intermediate-size surgery), or the goal-directed approach (major surgery). Children tolerate prolonged fasting poorly and preoperative fasting for clear fluids should not exceed 1 h. They have a greater tendency to develop hypoglycemia and hyponatremia than adults and, therefore, isotonic crystalloids that minimize these risks should be used during pediatric surgery. The basal daily need for fluid is children is usually taken according to the “4-2-1” rule to which additions can be made depending on the extent of the surgery. Intravenous fluid administration should be continued during the postoperative phase until enteral hydration is feasible.